A reconceptualization of fear of failure in entrepreneurship - Cacciotti, Gabriella; Hayton, James C.; Mitchell, J. Robert; Giazitzoglu, Andres (Journal of Business Venturing, 2016)
Fear of failure both inhibits and motivates entrepreneurial behavior and therefore represents a rich opportunity for better understanding entrepreneurial motivation. Although considerable attention has been given to the study of fear of failure in entrepreneurship, scholars in this field have investigated this construct from distinct disciplinary perspectives. These perspectives use definitions and measures of fear of failure that are potentially in conflict and are characterized by a static approach, thereby limiting the validity of existing findings about the relationship between fear of failure and entrepreneurship. The purpose of this paper is to delineate more precisely the nature of fear of failure within the entrepreneurial setting. Using an exploratory and inductive qualitative research design, we frame this construct in terms of socially situated cognition by adopting an approach that captures a combination of cognition, affect and action as it relates to the challenging, uncertain, and risk-laden experience of entrepreneurship. In so doing, we provide a unified perspective of fear of failure in entrepreneurship in order to facilitate progress in understanding its impact on entrepreneurial action and outcomes.